Interfractional variation in bladder volume and its impact on cervical cancer radiotherapy: Clinical significance of portable bladder scanner. Issue 7 (23rd June 2016) - Luo, Huanli; Jin, Fu; Yang, Dingyi; Wang, Ying; Li, Chao; Guo, Mingfang; Ran, Xueqi; Liu, Xianfeng; Zhou, Qi; Wu, Yongzhong
Abstract : Purpose: A constant bladder volume (BV) is essential to direct the radiotherapy (RT) of pelvic tumors with precision. The purpose of this study was to investigate changes in BV and their impact on cervical cancer RT and to assess the clinical significance of a portable bladder scanner (BS) in achieving a constant BV. Methods: A standard bladder phantom (133 ml) and measurements of actual urine volume were both used as benchmarks to evaluate the accuracy of the BS. Comparisons of BS with computed tomography (CT), cone‐beam CT (CBCT), and an ultrasound diagnostic device (iU22) were made. Twenty‐two consecutive patients with cervical cancer treated with external beam radical RT were divided into an experimental group (13 patients) and a control group (9 patients). In the experimental group, the BV was measured multiple times by BS pre‐RT until it was consistent with that found by planning CT. Then a CBCT was performed. The BV was measured again immediately post‐RT, after which the patient's urine was collected and recorded. In the control group, CBCT only was performed pre‐RT. Interfractional changes in BV and their impact on cervical cancer RT were investigated in both groups. The time of bladder filling was also recorded and analyzed. Results: In measuring the volume of the standard bladder phantom, the BS deviated by 1.4% in accuracy. The difference between the measurements of the BS and the iU22 had no statistical significance (linear correlation coefficient 0.96, P < 0.05). The BV measured by the BS was strongly correlated with the actual urine volume ( R = 0.95, P < 0.05), planning CT ( R = 0.95, P < 0.05), or CBCT ( R = 0.91, P < 0.05). Compared with the BV at the time of CT, its value changed by −36.1% [1 SD (standard deviation) 42.3%; range, −79.1%–29.4%] in the control group, and 5.2% (1 SD 21.5%; range, −13.3%–22.1%) in the experimental group during treatment. The change in BV affected the target position in the superior–inferior (SI) direction but had little or no effect in the anterior–posterior and right–left directions. Based on the collected data, the target displacement in the SI direction was reduced from 2.0 to 0.4 mm, while the CTV‐to‐PTV (CTV: clinical target volume; PTV: planning target volume) margin in the SI direction was reduced from 11.1 to 6.4 mm. The BV increased by 3.7 ± 1.0 ml/min (range, 1.7–4.7 ml/min), which depended on the amount of water ingested by the patient ( R = 0.96, P < 0.05). No correlation was found between the rate of urinary inflow and the patient's body mass. The authors were able to reduce the workload of measuring by using individual patient information including the patient's age, the water‐drinking amount, time at which water‐drinking began, and patient's diet. Conclusions: Changes in the BV have an influence on the RT of cervical cancer. A consistent and reproducible BV is acquired by using a portable BS, whereby the target displacement and CTV‐to‐PTV margin can be both reduced in the SI direction.